Gender bias in customer perceptions: The case of agro-input dealers in Uganda - De, Anusha; Miehe, Caroline; Van Campenhout, Bjorn (Elsevier, 2024)
CONTEXT Faced with incomplete and imperfect information, economic actors rely predominantly on perceptions and often base decisions on heuristics prone to bias. Gender bias in perceptions favoring men has been found in a variety of settings and may be an important reason why some sectors remain dominated by men and gender gaps in terms of benefits persist. In modernizing food supply chains in a patriarchal context such as the maize sub-sector in Uganda, this may result in women facing significant barriers to entry.